Diva [large type] - Goodwin, Daisy (Thorndike Press, a part of Gale, a Cengage Company, 2024)
"In the glittering and ruthlessly competitive world of opera, Maria Callas was known simply as la divina: the divine one. With her glorious voice, instinctive flair for the dramatic and striking beauty, she was the toast of the grandest opera houses in the world. But her fame was hard won: raised in Nazi-occupied Greece by a mother who mercilessly exploited her golden voice, she learned early in life to protect herself from those who would use her for their own ends. When she met the fabulously rich Greek shipping magnate Aristotle Onassis, for the first time in her life, she believed she'd found someone who saw the woman within the legendary soprano. She fell desperately in love. He introduced her to a life of unbelievable luxury, showering her with jewels and sojourns in the most fashionable international watering holes with celebrities like Elizabeth Taylor, Richard Burton and the Duke and Duchess of Windsor. And then suddenly, it was over. The international press announced that Aristotle Onassis would marry the most famous woman in the world, former First Lady Jacqueline Kennedy, leaving Maria to pick up the pieces. In this remarkable novel, Daisy Goodwin brings to life a woman whose extraordinary talent, unremitting drive and natural chic made her a legend. But it was only in confronting the heartbreak of losing the man she loved that Maria Callas found her true voice and went on to triumph"--